2019
DOI: 10.1002/ajim.22986
|View full text |Cite
|
Sign up to set email alerts
|

Work experiences of Latino building cleaners: An exploratory study

Abstract: Background: There are roughly 3.8 million cleaning workers in the United States. The cleaning workforce is largely composed of women, immigrants, and ethnic minorities who receive low wages and have low education levels. They are exposed to physical, chemical, biological, and psychosocial hazards.Methods: Qualitative methodology was used to investigate how Latino immigrants experience work as building cleaners. A grounded theory coding approach was used to analyze focus group data from 77 participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The reference lists of the included studies were screened and 8 of these papers met the eligibility criteria. Finally, 65 studies were included, of which 33 were quantitative (21-23, 25, 33, 40, 56-82), 23 were qualitative (24,32,34,37,41,43,44,(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and 9 were mixed-methods studies (26,35,38,39,42,84,(100)(101)(102). However, these studies were found to comply with the inclusion criteria with either only qualitative (35,38,39,42,84,101,102) or only quantitative findings (26,100).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference lists of the included studies were screened and 8 of these papers met the eligibility criteria. Finally, 65 studies were included, of which 33 were quantitative (21-23, 25, 33, 40, 56-82), 23 were qualitative (24,32,34,37,41,43,44,(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and 9 were mixed-methods studies (26,35,38,39,42,84,(100)(101)(102). However, these studies were found to comply with the inclusion criteria with either only qualitative (35,38,39,42,84,101,102) or only quantitative findings (26,100).…”
Section: Study Selectionmentioning
confidence: 99%
“…Migrants are especially vulnerable and likely to be exposed to precarious employment because of language barriers, employer prejudice and discrimination, lack of professional networks, lack of sufficient knowledge related to health and the labor system (32)(33)(34) and poor social support (35,36). In addition, migrant workers have been reported to be exposed to various forms of harassment at the workplace: prejudices by employers and workmates (33), unfair treatment and discrimination (37)(38)(39) or being forced to work or perform tasks that are incompatible with their contracts at the threat of deportation (37,(40)(41)(42). This situation is often worse in the case of undocumented migrants who are even more vulnerable and disadvantaged due to a lack of work or residency permits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Latino building cleaners found that there was widespread concern among participants about fear of job loss, unpaid or delayed wages, having multiple jobs, excessive workloads, stigma, psychosocial stress, enduring hazardous working conditions and working through WRII-but participants felt constrained by their documentation status to say nothing. 18 Additionally, some responses to the question on not filing a claim suggested that janitors are delaying care until the severity of their pain or injury reaches a certain point, as may be the case for complex musculoskeletal disorders. Better access to health care, and benefits including paid sick leave and vacation, and the ability to use those benefits, would be beneficial both to janitors' present health and in preventing the development of more severe sequelae.…”
Section: Wrii and Claim Filingmentioning
confidence: 99%
“…3 A focus group study of Latino cleaning workers found that many participants reported good health but in follow-up questions about their job, most also indicated having workrelated health problems. 18 The WA-BRFSS study also asked questions on amount of sleep per night, with <7 h considered inadequate; 84 the authors of that study found that 43.5% of janitors reported inadequate sleep, significantly higher than 33.4% of all other workers and 29.5% of nonworking adults. 3 A higher proportion, 55%, of survey respondents in the current JWS study reported inadequate sleep (Table 4), than in the WA-BRFSS results, and inadequate sleep was associated with an increase in the adjusted relative risk of WRII (Table 4) in our results.…”
Section: General Healthmentioning
confidence: 99%